PL02.4.A International validation study of an EORTC instrument measuring instrumental activities of daily living (IADL) in patients with brain tumours: EORTC IADL-BN32. (5th September 2022) - Oort, Q; Koekkoek, J; Aaronson, N K; Boele, F W; Brannan, C; Capela, A; Hjermstad, M; Klein, M; Lips, I; Narita, Y; Pace, A; Petranovic, D; et al.
Abstract: Background: Brain tumour patients often have neurocognitive deficits which can result in problems with activities in daily living that are cognitively complex. Currently, no valid and reliable brain tumour-specific instrument to measure these instrumental activities of daily living (IADL) is available, but such an instrument is being developed. This study aimed to validate the EORTC IADL-BN32 questionnaire, comprising five multi-item and two single item scales, in a large set of international brain tumour patients. Material and Methods: This international study was conducted in 10 countries worldwide. Primary and metastatic brain tumour patients and their proxies were requested to complete the EORTC IADL-BN32 and a subjective cognitive questionnaire (MOS COG-R) at multiple time points. Several psychometric properties were evaluated with baseline data, including the structural validity (bi-factor confirmatory factor analysis [CFA]), reliability (internal consistency), construct validity (known groups comparisons) and patient-proxy congruency (intra-class correlation coefficients [ICC], Spearman's correlation). Results: At baseline, 326 patients ( 30% low-grade glioma, 37% high-grade glioma (HGG) and 33% brain metastases) and 311 proxies completed the EORTC IADL-BN32. The bi-factor CFA was found to have a satisfactory model fit (CFI=0.92 and TLI=0.90), and other parameters indicated a good fit (RMSEA=0.08 and SRMR=0.05), thereby validating the preliminary scale structure, but also an IADL sum score. The multi-item scales showed good (0.9>α≥0.8) to excellent (α≥0.9) internal consistency (range α=0.86-0.97). Known groups comparisons analyses regarding patient's cognitive status (indications vs. no cognitive impairment), subjective cognitive complaints (MOS COG-R ≤30 vs. >30), basic ADL (Barthel Index <100 vs. 100) and performance status (KPS <70 vs. ≥70) showed significant differences on all IADL outcome measures in line with a priori defined hypotheses. On a group level, patient and proxy ratings had moderate to strong correlations, however, proxies tended to report more problems on all scales. The ICCs showed moderate to good congruency between patients and proxies (range ICC: 0.63-0.81). Conclusion: The evaluated psychometric properties support the current scale structure of the EORTC IADL-BN32. Additional psychometric properties with longitudinal data are needed, such as test-retest reliability and responsiveness, to further validate the EORTC-IADL BN32 questionnaire.